Lemierre's syndrome treated operatively. Issue 4 (1st October 2020) - Lanfear, Allison T.; Hamandi, Mohanad; Fan, Joy; Bolin, Madison L.; Williams, Michael; DiMaio, J. Michael; Waters, John
Abstract: Lemierre's syndrome (LS) is a pharyngeal infection complicated by infectious jugular vein thrombosis and septic emboli. Most commonly caused by Fusobacterium necrophorum, it may result in metastatic infection, especially when antibiotic treatment is delayed. Patients with LS are often healthy adults between 16 and 30 years who present with prolonged symptoms of pharyngitis, lateral neck pain, and fever. Other symptoms may include shortness of breath, tachycardia, and hypotension. When administered promptly, antibiotics can act as an effective treatment. However, complications may arise that require additional intervention. Herein, we report a case of LS in a young adult, complicated by severe pleural effusions that required surgical decortication.